NIKAH SIRI DALAM PERSPEKTIF MAQOSID AL-SYARI’AH IMAM AL-SYATIBI: KAJIAN KITAB AL-MUWAFAQAT - Mukti, Haeni; M. Thahir Maloko; Muhammad Shuhufi (Jurnal Diskursus Islam, 2026)
This study examines the practice of nikah siri (unregistered marriage) through the lens of the maqāṣid al-sharī‘ah of Imam al-Syāṭibī by analyzing the conceptual framework developed in al-Muwāfaqāt. Although nikah siri fulfills the classical juridical pillars and requirements of marriage, it generates various contemporary socio-legal issues, particularly those related to the protection of lineage (ḥifẓ al-nasl) and honor (ḥifẓ al-‘irḍ). This research employs a library-based method with both deductive and inductive qualitative approaches to explore the maqāṣid framework and its application to the issue of unregistered marriages. The findings indicate that, according to al-Syāṭibī, the formal validity of the marriage contract does not automatically align with the objectives of the law when the practice produces social harm, such as uncertainty regarding the status of the spouse and children, the absence of legal protection, and vulnerability to exploitation. The publicization of the marriage contract (i‘lān al-nikāḥ) is understood as an essential component of maqāṣid because it preserves social stability and lineage. In modern contexts, state registration functions as a logical extension of this objective. Nevertheless, al-Syāṭibī allows exceptions for nikah siri in situations of genuine necessity (ḍarūrah) or urgent need (ḥājah) that threaten life, honor, or legal access. Thus, nikah siri cannot be normalized as a general practice; rather, it is justified only in limited exceptional conditions that still uphold the overarching objectives of Islamic law. Keywords: Unregistered Marriage, Maqosid al-Syariah, Imam al-Shatibi, al-Muwafaqat.